A Research on the Handling Strategies of Fuzzy Information in Diplomatic Alternating Translation - Bai, Huinian (Pacific International Journal, 2025)
This study aims to solve the problem that fuzzy information in diplomatic consecutive interpreting may lead to inaccurate information transmission and even diplomatic disputes. First, it sorts out core concepts of consecutive interpreting, fuzzy information theory, and relevance theory to lay a theoretical foundation. Then, it systematically analyzes specific manifestations and causes of three common types of fuzzy information in diplomatic consecutive interpreting: semantic ambiguity, pragmatic ambiguity, and cultural ambiguity. Building on this typology, the study integrates the optimal relevance principle of relevance theory, the study explores practical strategies for handling these fuzzy information types, including translation techniques like addition and omission, and auxiliary tools such as note-taking, pauses, and speech rate control. Key findings show that taking optimal relevance as the core and flexibly combining translation strategies with auxiliary tools can effectively improve the accuracy of fuzzy information interpretation. The study provides theoretical guidance and practical references for interpreters to enhance their skills,and points out that future research can use empirical methods to compare interpreters of different proficiency levels in handling fuzzy information.